High diversity of root associated fungi in both alpine and arctic Dryas octopetala - Geml Jozsef; Ugland Karl; Høiland Klaus; Vrålstad Trude; Brysting Anne; Carlsen Tor; Bjorbækmo Marit; Schumacher Trond; Kauserud Håvard (BMC Plant Biology, 2010)
Abstract Background Dryas octopetala is a widespread dwarf shrub in alpine and arctic regions that forms ectomycorrhizal (ECM) symbiotic relationships with fungi. In this study we investigated the fungal communities associated with roots of D. octopetala in alpine sites in Norway and in the High Arctic on Svalbard, where we aimed to reveal whether the fungal diversity and species composition varied across the Alpine and Arctic regions. The internal transcribed spacer (ITS) region of nuclear ribosomal DNA was used to identify the fungal communities from bulk root samples obtained from 24 plants. Results A total of 137 operational taxonomic units (OTUs) were detected (using 97% similarity cut off during sequence clustering) and well-known ECM genera such as Cenococcum , Cortinarius, Hebeloma , Inocybe and Tomentella occurred frequently. There was no decrease in fungal diversity with increasing latitude. The overall spatial heterogeneity was high, but a weak geographical structuring of the composition of OTUs in the root systems was observed. Calculated species accumulation curves did not level off. Conclusions This study indicates that the diversity of fungi associated with D. octopetala does not decrease in high latitude arctic regions, which contrasts observations made in a wide spectrum of other organism groups. A high degree of patchiness was observed across root systems, but the fungal communities were nevertheless weakly spatially structured. Non-asymptotical species accumulation curves and the occurrence of a high number of singletons indicated that only a small fraction of the fungal diversity was detected.